Diversion in the Form of Protection of Human Rights - Arhjayati Rahim (Faculty of Law, Musamus University, 2019)
Crimes committed by children in Indonesia has reached its peak it signified the increasing rate of crimes committed by children. A dilemma when it comes to handling the perpetrators of crimes committed by children, on the other hand children are vulnerable creatures and tend not to be accountable as a result of his actions, on the other hand the child has committed a criminal offense that harm others. That many regulations that have been published to address the issue. The most recent is the Law No. 11 Year 2012 on child criminal justice system, which emphasizes the process of diversion in solving criminal cases involving children. Diversion destination is clear in Act No. 11 of 2012 concerning juvenile justice system Article 6 of diversion aims: Achieving peace victims and children, Resolving cases of children outside the judicial process, Protects children from the deprivation of liberty, Encouraging people to participate, Instill a sense of responsibility answer to this Child. Hal accordance with the principle of fulfillment of children's rights. So in this paper will discuss setting How Diversion Law as a form of Human Rights Protection. The existence of a diversion process in some cases of child crime that must be sought, it is hoped that in the future it will provide ideal and comprehensive protection for handling cases of children facing the law so that the fulfillment of children's rights both as victims and perpetrators can be carried out effectively and lead to fulfillment human rights because the truth is that human rights are inherent rights and exist in every human being and must be protected by the state